LONG‐TERM TAXON‐SPECIFIC RESPONSES OF MACROINVERTEBRATES TO DAM REMOVAL IN A MID‐SIZED SWEDISH STREAM. (29th June 2012) - Renöfält, B. M.; Lejon, A. G. C.; Jonsson, M.; Nilsson, C.
ABSTRACT Dam removal to restore ecologically impaired rivers is becoming increasingly common. Although the target often is to facilitate fish migration, dam removal has also been assumed to benefit other types of organisms. Because few studies thus far deal with effects of dam removal on stream macroinvertebrates and because results have been equivocal, we investigated both short‐ and longer‐term dam‐removal effects on downstream macroinvertebrate communities. We did this in a before‐and‐after study of the removal of a dam located in a south Swedish stream. We sampled the benthic fauna 6 months before dam removal and both 6 months and 3.5 years after the dam was removed. We compared species composition, taxonomic richness, total densities and densities of macroinvertebrate groups before and after dam removal and between downstream and reference sites. We found that dam removal reduced some macroinvertebrate taxa at the downstream site, but we found no effect on community composition. Although this corroborates results from previous short‐term studies, we also found a reduction of taxonomic richness and that some dam‐removal effects persisted or even increased over time. The most likely explanation for the suppression of benthic macroinvertebrate richness following dam removal is a significantly increased sediment transport from the former reservoir and a subsequent loss of preferred substrates. Our results indicate that adverse dam‐removal effects may be long lasting but taxon specific. We therefore call for longer‐term studies on a variety of organisms to better understand how dam removal may influence downstream macroinvertebrate communities. Copyright © 2012 John Wiley & Sons, Ltd.